2013
DOI: 10.1136/heartjnl-2012-303402
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes after percutaneous or surgical revascularisation of unprotected left main coronary artery-related acute myocardial infarction: a single-centre experience

Abstract: Thirty-day mortality was high in patients presenting with an ULMCA-related AMI, both in the PCI as in the CABG-treatment group. Presentation with cardiogenic shock, TIMI 0/1 flow on initial angiogram and diabetes mellitus were independently predicting of 30-day mortality, whereas treatment allocation was primarily determined by presentation with TIMI 0/1 flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 43 publications
2
22
0
Order By: Relevance
“…In a study comparing outcomes after percutaneous or surgical revascularisation of ULMCA-related AMI by Grundeken et al, the 30-day mortality rates of the PCI and CABG groups were 64% and 24%, respectively. (17) However, in Grundeken et al's study, there was an obvious bias regarding the selection of revascularisation strategy: for patients with TIMI Grade 0 or 1 in angiography, PCI was preferred over CABG. (17) The 2011 guideline for PCI from the American College of Cardiology Foundation (ACCF), American Heart Association (AHA), and Society for Cardiovascular Angiography and Interventions also pointed out that for STEMI in which distal coronary flow was TIMI Grade < 3, PCI can be performed more rapidly and safely than CABG (class IIa recommendation).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study comparing outcomes after percutaneous or surgical revascularisation of ULMCA-related AMI by Grundeken et al, the 30-day mortality rates of the PCI and CABG groups were 64% and 24%, respectively. (17) However, in Grundeken et al's study, there was an obvious bias regarding the selection of revascularisation strategy: for patients with TIMI Grade 0 or 1 in angiography, PCI was preferred over CABG. (17) The 2011 guideline for PCI from the American College of Cardiology Foundation (ACCF), American Heart Association (AHA), and Society for Cardiovascular Angiography and Interventions also pointed out that for STEMI in which distal coronary flow was TIMI Grade < 3, PCI can be performed more rapidly and safely than CABG (class IIa recommendation).…”
Section: Discussionmentioning
confidence: 99%
“…(17) However, in Grundeken et al's study, there was an obvious bias regarding the selection of revascularisation strategy: for patients with TIMI Grade 0 or 1 in angiography, PCI was preferred over CABG. (17) The 2011 guideline for PCI from the American College of Cardiology Foundation (ACCF), American Heart Association (AHA), and Society for Cardiovascular Angiography and Interventions also pointed out that for STEMI in which distal coronary flow was TIMI Grade < 3, PCI can be performed more rapidly and safely than CABG (class IIa recommendation). (18) Marso et al reported that the mortality during hospitalisation in the balloon angioplasty-only group (70%) and the stenting group (35%) differed significantly, proposing that stent implantation could improve the prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…Acute occlusion of the left main coronary artery is usually a fatal event, yet 4% of patients that arrive with STEMI and undergo PCI are reported to have left main narrowing and occlusion [58]. Reports of survival after acute total occlusion of left main coronary artery were rare prior to the thrombolytic era and therefore the report of the patient we treated in 1982 was published.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study, 55 patients underwent PCI (69% in cardiogenic shock) and 29 underwent CABG (28% in cardiogenic shock) for STEMI (78% PCI, 58% CABG) and NSTEMI/complete left bundle branch block with ULMCA culprit lesions . The PCI group had a higher prevalence of TIMI grade 0 flow (44% vs. 0%).…”
Section: Pci Versus Cabg For Ulmca Diseasementioning
confidence: 99%
“…A multivariate analysis showed that three factors were independent predictors of treatment allocation between PCI and CABG: TIMI 0/1 flow, distal bifurcation disease, and year of inclusion into the study . After excluding those with TIMI 0/1 flow, patients were more likely to undergo primary PCI if they had cardiogenic shock, and more likely to undergo CABG if they had distal ULMCA disease.…”
Section: Themes From These Studies: Old and Newmentioning
confidence: 99%